Maxillary Bone Regeneration Based on Nanoreservoirs Functionalized ε-Polycaprolactone Biomembranes in a Mouse Model of Jaw Bone Lesion. (26th February 2018) - Strub, Marion; Van Bellinghen, Xavier; Fioretti, Florence; Bornert, Fabien; Benkirane-Jessel, Nadia; Idoux-Gillet, Ysia; Kuchler-Bopp, Sabine; Clauss, François
Abstract : Current approaches of regenerative therapies constitute strategies for bone tissue reparation and engineering, especially in the context of genetical diseases with skeletal defects. Bone regeneration using electrospun nanofibers' implant has the following objectives: bone neoformation induction with rapid healing, reduced postoperative complications, and improvement of bone tissue quality. In vivo implantation of polycaprolactone (PCL) biomembrane functionalized with BMP-2/Ibuprofen in mouse maxillary defects was followed by bone neoformation kinetics evaluation using microcomputed tomography. Wild-Type (WT) and Tabby (Ta) mice were used to compare effects on a normal phenotype and on a mutant model of ectodermal dysplasia (ED). After 21 days, no effect on bone neoformation was observed in Ta treated lesion (4% neoformation compared to 13% in the control lesion). Between the 21st and the 30th days, the use of biomembrane functionalized with BMP-2/Ibuprofen in maxillary bone lesions allowed a significant increase in bone neoformation peaks (resp., +8% in mutant Ta and +13% in WT). Histological analyses revealed a neoformed bone with regular trabecular structure, areas of mineralized bone inside the membrane, and an improved neovascularization in the treated lesion with bifunctionalized membrane. In conclusion, PCL functionalized biomembrane promoted bone neoformation, this effect being modulated by the Ta bone phenotype responsible for an alteration of bone response.